The Effect of Watering Frequency on Growth, Productivity, and Agribusiness Feasibility of Bali Karet Shallot Variety in Lowland Areas - Ni Ketut Karina Sari; Ni Nyoman Alit Purnami; Dicky Marsadi (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2026)
This study aimed to evaluate the effect of watering frequency on the growth, productivity, and agribusiness feasibility of the Bali Karet shallot variety cultivated in lowland areas. The experiment was conducted at the Experimental Farm of the Faculty of Agriculture, Udayana University, from January to March 2026 using a Randomized Complete Block Design (RCBD) with four irrigation treatments: P0 (once/day), P1 (twice/day), P2 (three times/day), and P3 (soil moisture-based), each with three replications. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at the 5% significance level. Watering frequency significantly affected plant growth, productivity, water use, and agribusiness feasibility. Treatment P3 showed the best performance, increasing productivity from 7.8 to 11.3 t ha⁻¹ (44.9%), farm profit from IDR 17.4 million to IDR 42.6 million ha⁻¹ (144.8%), and the R/C ratio from 1.39 to 1.89, while reducing water consumption from 5,850 to 5,100 m³ ha⁻¹ (12.8%) compared with P0. These results demonstrate that soil moisture-based irrigation improves water-use efficiency while maximizing shallot productivity and profitability, making it a promising irrigation strategy for sustainable shallot production in lowland areas.